Developing an open access croplands research database through global collaboration - Olsen, Livia M. S.; Baillargeon, Tara; Maringanti, Harish (My University, 2012)
This article describes the processes, challenges, and outcomes of a project undertaken by Kansas State University (K-State) Libraries and a global community of researchers. The project, initiated by librarians in the newly created Faculty and Graduate Services Department, involved collaboration with a K-State agronomist. The initial concept was to create an open access database of croplands research submitted by researchers from the Global Research Alliance Croplands Research Group, a consortium of over 30 countries. Due to the project’s complexity, it was determined that a more manageable approach would be to pilot the project by including research from only the United States and Australia to resolve problems before scaling up to include all 34 countries in the GRA Croplands Research Group.
Keywords: Croplands; Databases; Collaboration; Solr; Global Research Alliance on agricultural greenhouse gasses; Open access